2012
DOI: 10.1073/pnas.1206069109
|View full text |Cite
|
Sign up to set email alerts
|

One influenza virus particle packages eight unique viral RNAs as shown by FISH analysis

Abstract: Influenza A virus possesses a segmented genome of eight negativesense, single-stranded RNAs. The eight segments have been shown to be represented in approximately equal molar ratios in a virus population; however, the exact copy number of each viral RNA segment per individual virus particles has not been determined. We have established an experimental approach based on multicolor single-molecule fluorescent in situ hybridization (FISH) to study the composition of viral RNAs at single-virus particle resolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
141
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 35 publications
8
141
0
Order By: Relevance
“…The observation that IAV can selectively reduce the relative packaging frequency of individual gene segments undermines the dogma that IAV genome segments are copackaged in equimolar ratios with high efficiency (9)(10)(11). Instead, packaging efficiency is clearly variable and can be modulated rapidly (via a singlenucleotide substitution) in response to selective pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that IAV can selectively reduce the relative packaging frequency of individual gene segments undermines the dogma that IAV genome segments are copackaged in equimolar ratios with high efficiency (9)(10)(11). Instead, packaging efficiency is clearly variable and can be modulated rapidly (via a singlenucleotide substitution) in response to selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…For IAV, it is widely believed that a single copy of each segment is packaged into progeny virions with nearly perfect efficiency, resulting in an equimolar ratio of the segments at the population level (9)(10)(11)(12). Confounding this model, we recently demonstrated that most IAV virions fail to express one or more gene products (13).…”
mentioning
confidence: 92%
“…We then excited the fluorophores attached to DNA molecules inside individual virus heads and the number of photobleaching steps was counted (Fig. S3) (27). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, an increasing number of reports provide convincing evidence to support the selective packaging model (28,50,51). The selective packaging model claims that each of eight vRNA segments possesses a segment-specific packaging signal sequence, allowing the selective incorporation of eight vRNA segments into a fully functional virion.…”
Section: Discussionmentioning
confidence: 99%